Regarding the Issue of Personal data Protection of Employees in Conditions of Digital Transformation - Spitsyna, Hanna; Polianskyi, Anton; Khlystun, Yuliia (Archives of Criminology and Forensic Sciences, 2022)
the specified article examines personal data, their list and history of occurrence, practice of application, their extension to labor relations, and guarantees of protection of personal data of the employee. It is noted that the personal data of an employee is a narrower concept than personal data and in connection with the lack of legal regulation of the protection of personal data of employees during their processing, urgent issues arise that require legal regulation by special legal norms, taking into account the practice of the EcHR and European experience. In addition, in the case of exercising the right to work, processing of personal data is carried out in accordance with the Labor Code of Ukraine, in which there are no special regulations regarding the specified mechanism, and other normative legal acts, an employment contract (contract), and not on the basis of a separate consent to the processing of personal data. It was concluded that the employee’s personal data require legal regulation from our state, and their processing by employer requires a clear mechanism and algorithm of actions capable of protecting the employee’s rights.